Gut Microbiota in Primary Sarcopenia: Mechanisms and Potential Therapeutic Targets - Leshan Chen; Youming Chen; Wenzhan Chen; Huiting Tan; Liuyan Ye; Jinsong Chen; Xuejuan Xu (Frontiers in Bioscience-Landmark, 2025)
As the global population ages, the risks associated with primary sarcopenia, including falls, fractures, functional decline, and frailty, are becoming increasingly apparent, all of which significantly impair the quality of life in older adults. Emerging evidence suggests that the gut microbiota plays a pivotal role in maintaining muscle physiology. Specific gut bacteria promote intramuscular protein synthesis through the production of certain amino acids (e.g., leucine, tryptophan), short-chain fatty acids (SCFAs), and hydrogen sulfide. Notably, Escherichia coli expressing the enzyme nicotinamidase (PncA) has been shown to enhance nicotinamide adenine dinucleotide (NAD+) synthesis, potentially improving mitochondrial function in muscle tissue. Furthermore, secondary bile acids and lactate influence the levels of fibroblast growth factor 15/19 and unacylated ghrelin in circulation by binding to receptors that are highly expressed in gut endocrine cells, thereby affecting muscle physiology. This review examines the characteristic composition of the gut microbiota in patients with sarcopenia, its role in primary sarcopenia, and potential therapeutic targets.